Putting people at heart: Namibian conservancies awarded - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Unlike the usual game reserves and national parks, Namibian conservancies allow residents to continue economic activities such as livestock and cattle farming and they are allowed to add wildlife use and tourism to their daily pursuits. Kathryn...